Analisis Semiotika Makna Toleransi terhadap Spectrum Autisme dalam Film Dancing In The Rain - Alfaidzi, Fahri Aula; Supriatno, Djoko (Program Studi Ilmu Komunikasi, 2023)
The film's message is a mechanism for signs that take the form of the message's contents, sound, or other elements in the brain of humans, language, dialogue, and others. Films cannot influence people to change attitudes, but films are quite influential on what people think, especially about something that is considered important, then it is chosen or even rejected according to personality factors that exist in society. This study uses Roland Barthes semiotic analysis method and also uses semiotic analysis theory to obtain an overview of the meaning of tolerance in the film Dancing In The Rain. The data collection techniques used are observation and documentation. Observations in this study were carried out by direct observation of research subjects, namely observation of audio-visual and images that have a meaning of tolerance in the film Dancing In The Rain. The Documentation Method is carried out by collecting relevant data such as the synopsis of the film, the trailer of the film. This study also found pieces of scenes that have a meaning of tolerance which the author analyzes using Analysis of Semiotics by Roland Barthes. The writer has discussed the denotation, connotation, & myth of the movie in the findings chapter.There are 3 meanings of tolerance in this film, namely helping, caring, and compassion, while intolerance in this film is scolding and bullying. This study recommends other research examining films and content that contains tolerance and society.